Pengembangan Media Pembelajaran Berbasis Aplikasi Quizizz pada Materi Teks Anekdot Kelas X SMK Negeri 3 Kediri - Achmad Fathoni Firmansyah; Rahmayantis, Marista Dwi; Sujarwoko (Universitas Insan Budi Utomo, 2025)
Interactive game-based learning media is a learning media equipped with moving images, sound and interactive games so that it can attract students' attention in participating in learning. This development aims to develop the use of the Quizizz game on student cohesion in anecdote text material. The population in this development research is class X Culinary 1,2 and 3 SMKN 3 Kediri with a total of 100 students. The implementation of this research adapts the development research design which is the basis for developing better products. The development model used in this study is a modification of the R2D2 model (Recursive, Reflective, Design, and Development). The development procedure includes determining, developing, and strengthening the product. The results of the validation of teaching materials obtained an average total value of 90%. Based on the validity and feasibility tests, the Quizizz application-based anecdotal text learning is declared very feasible to be used in Indonesian language learning at SMKN 3 Kediri. The main conclusion of this development research is that the development of learning media can be used to increase students' enthusiasm for learning in anecdote text material so that learning can be more meaningful and interesting for students.